Back of the book, back of the net: the comedy book indexes of Partridge and Toast. (March 2017) - Bain, Paula Clarke
Abstract : Paula Clarke Bain takes a look at the comedy book indexes of the spoof memoirs of established British TV comedy characters Alan Partridge and Steven Toast. The indexes are pretty laughable – but mostly for the right reasons.